The Ugnayan ng Pahinungod Roving Library - Marcelino, Neomi T. (2002)
This thesis was undertaken for the purposes of evaluating the existing collection and services being offered by the University of the Philippines Roving Library in Diliman, Quezon City. It also sought to suggest ways on how to improve the collection and services of the program through the establishment of a library that will house its collection. The concept of the bookmobile started in the United States. But here in the Philippines, we have our own counterparts. The Museo Pambata Foundation's Bookmobile and the National Bookstores Buklat-aklat Bookmobile are just two among others. Here, in our very own University of the Philippines, we have the Roving Library administered by the Ugnayan ng Pahinungod Diliman Chapter.